EPULLIS FISSURATUM - CLINICAL DOCTRINE IN THE SELECTION OF DIFFERENT SURGICAL TECHNIQUES - Gjorovska, Maja; Kacarska, Marina; Bajraktarova, Emilija; Gerasimova Pisevska, Sofija (Journal of Morphological Sciences; Vol 2 No 1 (2019): JMS, 2019)
Epulis fissuratum - fibrous inflammatory hyperplasia is a benign change in connective tissue that occurs as a result of chronic mechanical irritation caused by inadequate prosthetic devices. Treatment consists of excision of change and prosthetic rehabilitation. The aim of this paper was to present various surgical techniques performed at the Clinic for Oral Surgery, the advantages and disadvantages offered by each of them: conventional scalpel technique; laser technique; combined (scalpel / lasers). For this purpose, we present three cases where eupullis fissuratum was clinically registered. Individually, in each case we applied one of the surgical techniques, using local anesthesia, a basic surgical set, and an Er.Yag laser. The advantages offered by the laser technique in terms of intraoperative bleeding, postoperative flow and healing, which are a dry working field, absence of pain, swelling and redness, recovery of the surgical wound without scarring make the method of choice. The combined technique had an advantage over laser surgery only in terms of the speed of excision performed with a scalpel. Postoperative course and healing were equivalent to the laser technique.